The Politics of Written Language in the Arab World Writing Change - Høigilt, Jacob; Mejdell, Gunvor (Studies in Semitic Languages and Linguistics, 2017)
The Politics of Written Language in the Arab World asks how the central sociolinguistic notions of language ideology and diglossia are affected by the rapidly increasing amount of writing in the Arabic vernacular. Readership: Readers interested in the Arabic language situation, language ideology, diglossia, and emerging writing practices